Realising transition pathways for a more electric, low-carbon energy system in the United Kingdom: Challenges, insights and opportunities. (September 2017) - Chilvers, Jason; Foxon, Timothy J; Galloway, Stuart; Hammond, Geoffrey P; Infield, David; Leach, Matthew; Pearson, Peter JG; Strachan, Neil; Strbac, Goran; Thomson, Murray
The United Kingdom has placed itself on a transition towards a low-carbon economy and society, through the imposition of a legally-binding goal aimed at reducing its 'greenhouse gas' emissions by 80% by 2050 against a 1990 baseline. A set of three low-carbon, socio-technical transition pathways were developed and analysed via an innovative collaboration between engineers, social scientists and policy analysts. The pathways focus on the power sector, including the potential for increasing use of low-carbon electricity for heating and transport, within the context of critical European Union developments and policies. Their development started from narrative storylines regarding different governance framings, drawing on interviews and workshops with stakeholders and analysis of historical analogies. The quantified UK pathways were named Market Rules, Central Co-ordination and Thousand Flowers ; each reflecting a dominant logic of governance arrangements. The aim of the present contribution was to use these pathways to explore what is needed to realise a transition that successfully addresses the so-called energy policy ' trilemma, ' i.e. the simultaneous delivery of low carbon, secure and affordable energy services. Analytical tools were developed and applied to assess the technical feasibility, social acceptability, and environmental and economic impacts of the pathways. Technological and behavioural developments were examined, alongside appropriate governance structures and regulations for these low-carbon transition pathways, as well as the roles of key energy system 'actors' (both large and small). An assessment of the part that could possibly be played by future demand side response was also undertaken in order to understand the factors that drive energy demand and energy-using behaviour, and reflecting growing interest in demand side response for balancing a system with high proportions of renewable generation. A set of interacting and complementary engineering and techno-economic models or tools were then employed to analyse electricity network infrastructure investment and operational decisions to assist market design and option evaluation. This provided a basis for integrating the analysis within a whole systems framework of electricity system development, together with the evaluation of future economic benefits, costs and uncertainties. Finally, the energy and environmental performance of the different energy mixes were appraised on a 'life-cycle' basis to determine the greenhouse gas emissions and other ecological or health burdens associated with each of the three transition pathways . Here, the challenges, insights and opportunities that have been identified over the transition towards a low-carbon future in the United Kingdom are described with the purpose of providing a valuable evidence base for developers, policy makers and other stakeholders.